2020
DOI: 10.5327/z2176-947820190518
|View full text |Cite
|
Sign up to set email alerts
|

Estoque De Carbono E Agregação Do Solo Sob Fragmentos Florestais Nos Biomas Mata Atlântica E Cerrado

Abstract: Estudaram-se o estoque de carbono (EstC) e a agregação do solo no interior eno entorno de fragmentos florestais dos biomas Mata Atlântica (MA) e Cerrado(CE). Foram coletadas amostras de solo em quatro fragmentos florestais, doisna MA e dois no CE, nos quais foram amostrados três pontos internos: borda(BO), metade do raio (MR) e centro (CF), além de um ponto no entorno;sistema plantio direto (SPD) e pastagem permanente (PP) na MA e no CE,respectivamente. Determinaram-se o carbono orgânico total (COT), a densida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 48 publications
2
19
0
5
Order By: Relevance
“…O entendimento do processo da formação estrutural do solo envolve a compreensão da interação dos aspectos biológicos, químicos, geológicos e físicos no contexto do ambiente edáfico. A estabilidade dos agregados pode ser compreendida como um reflexo da estrutura do solo por ser dependente do equilíbrio integrado desses fatores CECAGNO;BAYER, 2019;MELO et al, 2019;OZÓRIO et al, 2019).…”
Section: Introductionunclassified
“…O entendimento do processo da formação estrutural do solo envolve a compreensão da interação dos aspectos biológicos, químicos, geológicos e físicos no contexto do ambiente edáfico. A estabilidade dos agregados pode ser compreendida como um reflexo da estrutura do solo por ser dependente do equilíbrio integrado desses fatores CECAGNO;BAYER, 2019;MELO et al, 2019;OZÓRIO et al, 2019).…”
Section: Introductionunclassified
“…Barros and Fearnside (2016), studying carbon stock (C) on the edges of forest fragments in the Amazon biome, reported an increase in soil C stock in the first meters entering the fragments, when compared to areas of 300 meters within these fragments. However, studies that present the effects that fragmentation and edge effect can cause in C and in the edaphic characteristics of Brazilian biomes are still incipient in the literature (Ozório et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the 0.05-0.10m layer, the SC, PP, and NTS presented contents of 11.63, 13.71, and 12.57 g kg -1 , respectively. These higher contents in the NF area are due to the higher litter deposition of different forest extracts (Ozório et al, 2019), which increases the TOC contents in the most superficial layers of the soil (Assunção et al, 2019). Several authors have reported higher TOC contents in higher native areas compared with production systems in different regions of Brazil, soil types, and management systems (Borges et al, 2019;Maia et al, 2019;Santos et al, 2019;Ferreira et al, 2020;Medeiros et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of natural areas into production systems can, in addition to modifying the landscape, change the edaphic quality when not properly handled (Freitas et al, 2018). The different uses and managements directly influence soil attributes, such as carbon (C) (Lal, 2018;Ozório et al, 2019), besides causing changes in physical (Sales et al, 2018;Falcão et al, 2020), chemical (Souza et al, 2018;Assunção et al, 2019), and biological attributes of the soil (Borges et al, 2015;Barbosa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%